Effectiveness of the Implementation of the 2024 General Election with the Use of the Recapitulation Information System - Ramadan, Muhammad Fitrah; Saputra, Imran Eka; Arifin, Muhammad Yarif (Qawanin Jurnal Ilmu Hukum, 2025)
This study aims to determine and analyze the Effectiveness of the Implementation of the 2024 General Election with the Use of the Recapitulation Information System and to determine and analyze the factors that influence the implementation of the 2024 general election with the use of the Recapitulation Information System. This study uses an empirical legal research method, with the research location in Makassar City and its location at the General Election Commission of South Sulawesi Province. Data was collected through interview techniques and literature studies, which were then analyzed qualitatively descriptively. The results of the study indicate that the Effectiveness of the Implementation of the 2024 General Election with the Use of the Recapitulation Information System has not been fully effective because there are still many obstacles that hinder the use of the Recapitulation Information System such as inadequate networks, devices that are not supportive. In addition, many Voting Organizer Groups still do not understand and understand the Recapitulation Information System. As a recommendation in order to increase the Effectiveness of the Use of the Recapitulation Information System in the General Election, the government needs to add and update facilities and infrastructure, especially those related to networks and devices. The General Election Commission of the Republic of Indonesia needs to upgrade the Recapitulation Information System so that it is easy to access. The General Election Commission of South Sulawesi Province needs to provide special training to the Voting Organizing Groups. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis Efektivitas Pelaksanaan Pemilihan Umum Tahun 2024 dengan Penggunaan Sistem Informasi Rekapitulasi dan untuk mengetahui serta menganalisis faktor-faktor yang memengaruhi pelaksanaan pemilihan umum Tahun 2024 dengan penggunaan Sistem Informasi Rekapitulasi. Penelitian ini menggunakan metode penelitian hukum empiris, dengan lokasi penelitian di Kota Makassar dan tempatnya di Komisi Pemilihan Umum Provinsi Sulawesi Selatan. Data dikumpulkan melalui Teknik wawancara dan studi pustaka, yang kemudian di analisis secara kualitatif deskriptif. Hasil penelitian menunjukkan bahwa Efektivitas Pelaksanaan Pemilihan Umum Tahun 2024 dengan Penggunaan Sistem Informasi Rekapitulasi belum sepenuhnya efektif dikarenakan masih banyak kendala yang menghambat penggunaan Sistem Informasi Rekapitulasi seperti jaringan yang kurang memadai, perangkat yang kurang mendukung. Di tambah dengan Kelompok Penyelenggara Pemungutan Suara masih banyak yang belum mengerti dan paham dengan Sistem Informasi Rekapitulasi. Sebagai rekomendasi dalam rangka meningkatkan Efektivitas Penggunaan Sistem Informasi Rekapitulasi pada Pemilihan Umum agar pemerintah perlu menambah dan memperbaharui sarana dan prasarana terutama yang berkaitan dengan jaringan dan perangkat. Komisi Pemilihan Umum Republik Indonesia perlu mengupgrade Sistem Informasi Rekapitulasi sehingga mudah untuk diakses. Komisi Pemilihan Umum Provinsi Sulawesi Selatan perlu mengadakan pelatihan khusus kepada para Kelompok Penyelenggara Pemungutan Suara.